2009
DOI: 10.1007/s11103-009-9566-y
|View full text |Cite
|
Sign up to set email alerts
|

RA68 is required for postmeiotic pollen development in Oryza sativa

Abstract: Postmeiotic development is a unique characteristic of flowering plants. During the development, microspores undergo two cycles of mitosis (PMI and PMII) and a subsequent maturation process to finally produce the mature pollen, but the mechanism underlying the development is still largely unknown. Here, we report on the roles of a novel gene, RA68, in postmeiotic pollen development in Oryza sativa. RA68 was expressed preferentially in shoots and flowers. In flowers, the transcript persisted from the floral orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…We found no differences in the tapeta from OsPCBP-RI versus WT plants, thereby excluding the possibility that tapetal lesions lead to pollen abortion and arrested development due to anther abnormalities. RA68 is required for postmeiotic pollen development by affecting starch accumulation (Li et al 2010). This further confirms that pollen abortion is caused by transcriptional arrest of OsPCBP, i.e., because of the deletion of OsPCBP.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We found no differences in the tapeta from OsPCBP-RI versus WT plants, thereby excluding the possibility that tapetal lesions lead to pollen abortion and arrested development due to anther abnormalities. RA68 is required for postmeiotic pollen development by affecting starch accumulation (Li et al 2010). This further confirms that pollen abortion is caused by transcriptional arrest of OsPCBP, i.e., because of the deletion of OsPCBP.…”
Section: Discussionsupporting
confidence: 73%
“…RTS (Luo et al 2006) andOsSCP1, OsSCP2, andOsSCP3 (Park et al 2006) also have been characterized. PIP1, a pollen-preferential gene from rice, is another regulator of late pollen development (Han et al 2006) as is the postmeiotic RA68 (Li et al 2010).…”
mentioning
confidence: 99%
“…By contrast, RA68 gene, which encodes a protein with unknown function in rice, is expressed in the tapetum and in developing spores. Pollen grains of RA68 RNAi plants were arrested in the mid/late uninucleate microspore stage, or microspore mitosis (Li et al, 2010b). OsRAD21-3, one of four rice RAD21-related genes, is expressed in pollen grains.…”
Section: Discussionmentioning
confidence: 99%
“…OsRAD21-3, one of four homologs of radiation-sensitive (RAD) mutant 21 of the fission yeast in the rice genome, is preferentially expressed in microspores and pollen grains and is required for postmeiotic pollen development (Tao et al, 2007). The RA68 gene, with unknown function, is expressed preferentially in shoots and flowers, and RNAi plants of RA68 are defective in microspore mitosis and starch accumulation (Li et al, 2010b). The mutant pollen grains of SUC TRANSPORTER1 and rice IMPORTIN b1, which encodes an importin-b protein involved in the import of nuclear proteins, matured normally, but reciprocal cross experiments between heterozygous mutants and wild-type plants clearly showed that mutant alleles could not be transmitted through the male gametophyte, suggesting that the pollen grains of the mutant plants were dysfunctional (Hirose et al, 2010;Han et al, 2011).…”
mentioning
confidence: 99%
“…In wda1, epicuticular wax crystals were absent in the outer layer of the anther, and the microspore development was severely retarded and finally disrupted as a result of defective pollen exine formation. These findings provide interesting information on the role of waxes in OsRA68 AY568677 Proline-and threonine-rich protein Postmeiotic pollen development Li et al (2009) microspore exine development of the tapetum and anther expansion ). The pollen-preferential gene, RICE IMMATURE POL-LEN 1 (RIP1), was isolated from a T-DNA insertional population.…”
Section: The Developmental Process Of Male Reproductive Organ In Ricementioning
confidence: 91%